A chemical-free approach for effective abatement of acetochlor in drinking water - Xinyuan Yi; Yue Du; Zhixuan Tan; Wanxin Li; Ran Yin (Journal of Hazardous Materials, 2026)

Subchronic PM2.5 exposure exacerbates chronic stress-induced depression-like pathology in mice - Haoyu Lu; Xiaohui Zhao; Ran Ning; JunKoo Yi; Zhongmei He; Yan Zhao; Jianan Geng; Jia Zhou; Weijia Chen; Rui Du (Environmental Research, 2026)

pH-responsive metal–organic framework–iron scaffolds for antibacterial and osteogenesis-promoting applications in diabetic infected bone defects - Yaxin Xue; Xinyu Ran; Danyang Zhao; Jian Wang; Hao Jiang; Chengji Wang; Wei Xu; Hao Lv; Zhencheng Yu; Zijing Du; Yi Cao; Dongmei Dong; et al. (Chemical Engineering Journal, 2026)

Effect of overlying low-permeable soil on underwater shield tunnel response to water level fluctuation - Dong-Mei Zhang; Hao-Ran Lai; Yi-Yao Shen; Feng Du (Tunnelling and Underground Space Technology, 2026)

The effect of high-pressure homogenization pressure on the 3D printing of potato protein secondary emulsion - Yi Liu; Hao-ran Chen; Ao-xue Qie; Chong-hao Bi; Zhi-gang Huang; Quan-lai Li; Qiu-yue Du (Food and Bioproducts Processing, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Tailoring the microenvironment of ruthenium centers at poly(ionic liquid) frameworks for mild reverse water gas shift reaction - Rui Wang; Yi-Ran Du; Jia-Ni Li; Jing-Wen Sun; Zhao-Rong Yan; Bao-Hua Xu (Chemical Engineering Journal, 2026)

A LLM-based agent for the construction of typhoon knowledge graphs - Yi Huang; Yongqi Xia; Ran Tao; Donglai Jiao; Xiangqiang Min; Jieying Zheng; Yuting Jiang; Wenjun Wu; Peijun Du (Environmental Modelling & Software, 2026)

Responses of carbon monoxide photoproduction in surface seawater to environmental changes under simulated solar radiation - Xuan Ji; Ming-Liang Zhao; Yi-Ran Jia; Cai-Jie Zhang; Qi-Mei Du; Jing Zhang; Gui-Peng Yang (Marine Chemistry, 2026)

Enhanced removal of cytotoxicity from wastewater by silica gel-activated ferrate (VI) - Si-Yi Shi; Yao Lu; Yi-Ran Wan; Chang-Jie Yuan; Wei Hu; Min Liu; Ying Chen; Ye Du (Journal of Hazardous Materials, 2026)

Regulatory mechanisms of total phosphorus on N2O concentrations: A case study of Dongting lake - Jie Liang; Yi Li; Weixiang Li; Ziqian Zhu; Xiang Gao; Ran Du; Lan Lu; Jing He; Chaozhong Tan; Rong Wu; Jikai Liao (Water Research, 2025)

Chloride ion-driven activation of Ru-CeO2 for efficient methoxycarbonylation of long-chain alkenes - Yi-Ran Du; Yi-Yu Tao; Jing-Wen Sun; Han-Sheng Li; Rui Zhang; Bao-Hua Xu (Chemical Engineering Journal, 2025)

CCP domain containing protein from complement factor H of Paralichthys olivaceus has potential effects against Edwardsiella piscicida infection - Xuan-yue Wang; Yu-ting Du; Xin-yi Jiang; Zhuo-ran Ma; Chao-ran Zhang; Xue-peng Li; Zeng-zhi Yuan; Mo-fei Li (Aquaculture, 2025)

A comprehensive omics resource and genetic tools for functional genomics research and genetic improvement of sorghum - Chengxuan Chen; Fengyong Ge; Huilong Du; Yuanchang Sun; Yi Sui; Sanyuan Tang; Zhengwei Shen; Xuefeng Li; Huili Zhang; Cuo Mei; Peng Xie; Chao Li; et al. (Molecular Plant, 2025)

A genomic variation map provides insights into potato evolution and key agronomic traits - Qun Lian; Yingying Zhang; Jinzhe Zhang; Zhen Peng; Weilun Wang; Miru Du; Hongbo Li; Xinyan Zhang; Lin Cheng; Ran Du; Zijian Zhou; Zhenqiang Yang; et al. (Molecular Plant, 2025)

Highly dispersed WOm enables efficient reductive debenzylation of hexabenzylhexaazaisowurtzitane (HBIW) over bifunctional Pd-WOm/CeO2 - Qing-Shan Niu; Yi-Ran Du; Xin-Peng Guo; Jing-Wen Sun; Si-Ping Pang; Bao-Hua Xu (Chemical Engineering Journal, 2025)

Numerical simulation of tracer breakthrough curves in karst aquifers by a coupled discrete-continuum model - Xiaokang Zheng; Zhibing Yang; Shuangqiao Zhan; Xingwu Du; Yuncai Chen; Ran Hu; Yi-Feng Chen (Journal of Hydrology, 2024)

Molecular epidemiology of herpangina in the subcenter of Beijing, China: a surveillance study during 2021-2022 - Wan-Xue Zhang; Lin Zou; Yan Cui; Yiguo Zhou; Shan-Shan Zhang; Han Yang; Susu Ding; Qin-Yi Ma; Lu Xi; Ran-Ran Zheng; Juan Du; Jianming Zhang; et al. (Archives of Virology, 2024)

Associations between exposure to phthalates and liver function among women undergoing assisted reproductive technology - Yi Wang; Li Yin; Yao-Yao Du; Hong-Mei Liao; Juan Li; Wen Yao; Xiao-Qiong Yuan; Qing-Chun Guo; Tao-Ran Deng; Na Guo; Min Zhang; Qiang Zeng; et al. (Environmental Toxicology and Pharmacology, 2024)

Ru-Ni bimetallic catalyst supported on CeO2 boosts chemoselective methoxycarbonylation of olefins - Yi-Ran Du; Rui Wang; Qing-Shan Niu; Yi-Yu Tao; Bao-Hua Xu (Chemical Engineering Journal, 2024)

Deep Sc-RNA sequencing decoding the molecular dynamic architecture of the human retina - Lulin Huang; Runze Li; Lin Ye; Shanshan Zhang; Huaping Tian; Mingyan Du; Chao Qu; Shujin Li; Jie Li; Mu Yang; Biao Wu; Ran Chen; et al. (Science China Life Sciences, 2023)

Efficient electrocatalytic reduction of CO2 to CO on highly dispersed Ag nanoparticles confined by Poly(ionic liquid) - Guo-Yi Duan; Xiao-Qiang Li; Yi-Ran Du; Bao-Hua Xu (Chemical Engineering Journal, 2023)

Identification and detection sensitivity of Microcystis aeruginosa from mixed and field samples using MALDI-TOF MS - Li-Wei Sun; Wen-Jing Jiang; Jun-Yi Zhang; Wen-Qian Wang; Yang Du; Hiroaki Sato; Masanobu Kawachi; Ran Yu (Environmental Monitoring and Assessment, 2018)

Knockdown of hippocampal cysteinyl leukotriene receptor 1 prevents depressive behavior and neuroinflammation induced by chronic mild stress in mice - Xu-Ben Yu; Rong-Rong Dong; Hui Wang; Jing-Ran Lin; Yun-Qi An; Yong Du; Su-Su Tang; Mei Hu; Yan Long; Hong-Bin Sun; Ling-Yi Kong; Hao Hong (Psychopharmacology, 2016)

A novel species of ellipsoidal multicellular magnetotactic prokaryotes from L ake Y uehu in C hina - Yi‐Ran Chen; Rui Zhang; Hai‐Jian Du; Hong‐Miao Pan; Wen‐Yan Zhang; Ke Zhou; Jin‐Hua Li; Tian Xiao; Long‐Fei Wu (Environmental Microbiology, 2015)
Summary Two morphotypes of multicellular magnetotactic prokaryotes ( MMPs ) have been identified: spherical (several species) and ellipsoidal (previously one species). Here, we report novel ellipsoidal MMPs that are ∼ 10 × 8 μm in size, and composed of about 86 cells arranged in six to eight interlaced circles. Each MMP was composed of cells that synthesized either bullet‐shaped magnetite magnetosomes alone, or both bullet‐shaped magnetite and rectangular greigite magnetosomes. They showed north‐seeking magnetotaxis, ping‐pong motility and negative phototaxis at a velocity up to 300 μm s −1 . During reproduction, they divided along either their long‐ or short‐body axes. For genetic analysis, we sorted the ellipsoidal MMPs with micromanipulation and amplified their genomes using multiple displacement amplification. We sequenced the 16 S r RNA gene and found 6.9% sequence divergence from that of ellipsoidal MMPs , Candidatus Magnetananas tsingtaoensis and > 8.3% divergence from those of spherical MMPs . Therefore, the novel MMPs belong to different species and genus compared with the currently known ellipsoidal and spherical MMPs respectively. The novel MMPs display a morphological cell differentiation, implying a potential division of labour. These findings provide new insights into the diversity of MMPs in general, and contribute to our understanding of the evolution of multicellularity among prokaryotes.